Transformation of Makassar Container Terminal to Improve Loading and Unloading Affecting Logistics Costs - Jumriani, Jumriani; Hamsah, Hamsah; Rahmah Abu, Sitti; Sanitad, Ni Made Divya (Universitas of Muhammadiyah Makassar, 2024)
The container terminal is essential in marine logistics as the connection between sea and land. The acceleration of economic globalization and regional economic integration leads to a substantial rise in commerce. This study aims to determine the process and impact of the Makassar container terminal transformation and what obstacles hinder the smoothness of the transformation process in the Container of PT. Pelindo Regional IV Makassar Branch. This study used qualitative research through direct observation of the Object being investigated or directly witnessing the actual situation, as well as interviews with PT Pelindo IV Makassar Branch employees. The study results show that 1) Transformation in the Makassar container terminal is a strategic step to increase ports’ efficiency, capacity, and competitiveness in eastern Indonesia. With advanced technology, operational optimization, and government policy support, this terminal can improve loading and unloading performance, reduce logistics costs, and support regional economic growth. 2) Several major obstacles were still found in the transformation process faced by the Makassar container terminal, consisting of a) Resource aspects, namely the standard of understanding that is not yet qualified and the readiness of human resources is not 100% to support the transformation program; b) business processes, still need improvement in SOP, PNC, GATE, Yard, Berth, Customer Service and Safety; c) Equipment and Facilities, some equipment is damaged so that it cannot be used optimally; d) Wavy field conditions; e) Layout and markings on the field are absent and f) Information and Technology (IT) system used did not fully support operational activities. It can be concluded that the transformation process continues to improve services for shipping companies, which are its main customers. The implication of the study is that service standards in the container terminal area are the company’s main concern in providing optimal and efficient services.